PREPARATION AND EVALUATION OF DEEP CLEANSING EXFOLIATOR - X, Fatima Grace; B, Anbarasan; T, Kanimozhi; S, Shanmuganathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objective of the present study is to formulate an exfoliant using natural ingredients along with diatoms. Skin care products are important factor to improve confidence in individuals. Health of an individual is mainly represented by skin which is the major part of the body. Skin can be affected by several environmental factors such as ultraviolet rays, pollution, dust, and climatic changes that can intensify issues related to skin. Environmental causes can be prevented from skin damage by treating with topical application of synthetic or herbal cosmetics. Methods: In this preparation, diatoms are used, derived from marine phytoplankton which may contain a small quantity of muddy sludge, sand, and debris. Other natural ingredients are kiwi fruit, almond, and coffee seeds. Esthetic ingredients used in this preparation include pH modifiers, viscolysers, and surfactants. Among these ingredients, diatoms and coffee seeds attribute to the exfoliating activity of the preparation. Results: The prepared gel was evaluated for various parameters such as color, odor, consistency, pH, viscosity, spreadability, washability, grittiness, foamability, irritability, and extrudability. The results were found to be satisfactory. Conclusion: The present work was attempted to make a herbal exfoliant using suitable base to form a gel. Since diatoms are natural exfoliating agent, they are incorporated into the formulation which increases the efficiency of the product. Various parameters have been evaluated providing satisfactory result and improve the appearance of the skin without any side effects.